Developmental validation of the EZ1&2™ DNA Investigator® Kit on the EZ2® Connect Fx. (December 2022) - Scherer, Mario; Terramagra, Daniele; Liberty, Amy; Prochnow, Anke
Abstract: The EZ1&2 DNA Investigator Kit allows automated purification of total DNA from forensic and human identity samples on the EZ2 Connect Fx instrument. Its proven magnetic-bead technology provides high-quality DNA, suitable for direct use in sensitive downstream applications such as quantitative PCR, STR analysis and NGS. The purified DNA obtained is free of proteins, nucleases and inhibitors. In this study, the performance of the EZ1&2 DNA Investigator Kit on the EZ2 Connect Fx was evaluated using typical casework sample types and conditions commonly encountered in forensic and parentage laboratories. Wherever applicable, this validation study followed the recommendations of the European Network of Forensic Science Institutes (ENFSI) and the validation guidelines of the Scientific Working Group on DNA Analysis Methods (SWGDAM).